High prevalence of myocarditis in patients with hypertensive heart disease and cardiac deterioration - Frustaci, Andrea; Francone, Marco; Petrosillo, Nicola; Chimenti, Cristina (European journal of heart failure, 2013)
Aims Structural abnormalities causing cardiac deterioration in hypertensive heart disease (HHD) are poorly understood. The aim of the study was to evaluate left ventricular (LV) myocardial changes in patients with HHD and cardiac failure. Methods and results Among 1229 patients undergoing an LV or biventricular endomyocardial biopsy because of unexplained LV dysfunction from 2000 to 2010, 45 had HHD. The HHD population had non‐invasive assessment of cardiac wall thickness, diameters, and function; endomyocardial samples were processed for histology, immunohistochemistry, and polymerase chain reaction (PCR) for cardiotropic viruses. Mean LV end‐diastolic diameter was 63.3 ± 5.9 mm, LV ejection fraction 29.7 ± 7.6%, and maximal wall thickness 12.8 ± 0.9 mm. At histology, hypertrophy with degeneration of cardiomyocytes, increased external/lumen ratio of intramural arterioles, and myocardial fibrosis were observed in 17 patients (38%). In the remaining 28 patients (62%), these histological changes were associated with myocarditis. Myocarditis was present in 40.4% of the cohort without HHD. PCR was negative in HHD without inflammation while it was positive in 10 subjects with myocarditis (enterovirus in 3 cases, adenovirus 4, influenza virus 3). Addition of immunosuppression to supportive therapy in the 18 virus‐negative myocarditis subjects was followed at 6 months by significant recovery of LV function in 15 (83%; ejection fraction from 25.3 ±9.3% to 49.5 ±9.8%) while LV function improved to a minor extent (ejection fraction from 25 ± 5.1% to 36 ± 4.4%) in 12 of 27 patients (44%) on supportive treatment alone. Conclusion Myocarditis is a major cause of cardiac deterioration in patients with HHD; its recognition may improve patient treatment and outcome.